Caracterização molecular do mecanismo de interação de quitosanas com bicamadas lipídicas compostas de dipalmitoilfosfatidilcolina - Cunha, Richard André (2013)
Chitosan is a versatile macromolecule with total biocompatibility, biodegradability and a cationic character which makes it suitable to biomedical applications (tissue engineering: skin, bones, neural cell and liver), as well to biopharmaceutical (drug and gene delivery). The information presented by experimental techniques remains unclear about the molecular events that are related with the biological activity of chitosan, and most of them, are limited to describe macroscopic properties. In the present work, simulations of molecular dynamics simulations were used in order to describe the interaction between the chitosan and models of biological membranes made by units of dipalmitoylphosfatidylcholine (DPPC). These phospholipids, in particular, could be largely found in biological membranes, playing an important role in the cells membranes. In order to describe the molecular behavior of the chitosan and DPPC in the simulations, were used parameters recently developed or improved. The initial systems were built by putting a variable amount of chitosan chains, with 20% of acetylation degree, at a few angstroms of the DPPC bilayer, in explicit solvent. The relation between the quantity of chitosan and the number of water molecules, aims to reproduce the chitosan concentration of 10, 30 e 50 mg/mL. The simulations were made by 100 ns for the DPPC only, 150 ns for the 10 mg/mL and 250 ns for the concentration of 30 and 50 mg/mL. The results suggest that the biological action mechanism of the chitosan on lipids bilayers cannot be explained only by electrostatic interactions. The simulations help to describe the role of the polar groups in the chitosan DPPC interactions, as well their relationship with the solvent. Thereby, the hydrogen bond plays an important role such as the pure electrostatic interactions, and this interaction mechanism also depends on factors such as the chitosan concentration and the relation with water. The increase in the chitosan concentration is closely dependant on the effectiveness of specific interactions, that are driven by the competition between the interactions of the type chitosan chitosan, and chitosan-DPPC. The N-acetylglicosamine residues, showed to have an important role on the chitosan action in the membrane, with a concentration dependant influence. The chitosan inflicts structural alterations in the supramolecular organization of the membrane, and properties such as area per lipid and order parameter of the carbons in the aliphatic chain, which are drastically affected by the chitosan concentrations of 30 and 50 mg/mL.